Slurry, method for manufacturing electrode, and method for manufacturing battery
By using a combination of carbon black slurry with a specific particle size distribution in lithium-ion secondary batteries, a combination of binding agent and active substances, an excellent electrode is formed, which solves the problem of insufficient discharge rate and cycling characteristics of lithium-ion secondary batteries, and significantly improves the The performance and peel strength of the battery are provided.
Patent Information
- Application Number
- CN202380044411.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-08
- Filing Date
- 2023-04-06
- Publication Date
- 2025-01-10
AI Technical Summary
The discharge rate and cycle characteristics of the existing lithium-ion secondary batteries are insufficient, and the peel strength between the mixture layer and the current collector is poor, making it difficult to meet the needs of high energy density and stable power supply.
The volume reference particle size distribution of the particle group formed by combining the secondary and tertiary particles of carbon black in a liquid medium is determined by laser diffraction and scattering method, and the binding agent and active substance are combined. , excellent electrodes are formed, and conductivity and peel strength are improved.
The discharge rate characteristics and cycle characteristics of lithium-ion secondary batteries are achieved, and the peel strength between the mixture layer and the current collector is significantly improved, which improves the overall performance of the battery.
Smart Images

Figure CN119301776A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a slurry, an electrode and a method for producing a battery. Background Art
[0002] As environmental and energy issues continue to become more prominent, the development of technologies for realizing a low-carbon society that reduces dependence on fossil fuels is being actively promoted. Such technological developments include the development of low-pollution vehicles such as hybrid electric vehicles and electric vehicles, the development of natural energy power generation and storage systems such as solar power generation and wind power generation, and the development of next-generation power supply networks that efficiently supply electricity and reduce power supply losses.
[0003] One of the key components commonly required in these technologies is a battery, and for such a battery, a high energy density is required to miniaturize the system. In addition, a high discharge rate characteristic is required to be able to provide stable power supply without being affected by the ambient temperature. Moreover, good cycle characteristics that can withstand long-term use are also required. Therefore, the replacement of lithium-ion secondary batteries with higher energy density, discharge rate characteristics and cycle characteristics from conventional lead-acid batteries, nickel-cadmium batteries, and nickel-hydrogen batteries is progressing rapidly.
[0004] In the past, the positive electrode of a lithium-ion secondary battery was manufactured by applying a positive electrode paste containing a positive electrode active material, a conductive material, and a binder (also called a binder) to a current collector. As the positive electrode active material, lithium-containing composite oxides such as lithium cobalt oxide and lithium manganese oxide are used. In addition, since the positive electrode active material lacks conductivity, a conductive material such as carbon black is added to the positive electrode paste for the purpose of imparting conductivity (for example, Patent Document 1).
[0005] Prior art literature
[0006] Patent Literature
[0007] Patent Document 1: Japanese Patent Application Publication No. 2008-227481 Summary of the invention
[0008] Problems to be solved by the invention
[0009] In recent years, there has been a demand for further improvement in the performance of batteries such as lithium ion secondary batteries.
[0010] The present invention aims to provide an electrode containing carbon black, having excellent discharge rate characteristics and cycle characteristics, and having excellent peel strength between a mixture layer and a current collector, and a slurry useful for battery formation. The present invention also aims to provide a method for manufacturing an electrode and a method for manufacturing a battery using the slurry.
[0011] Means for solving problems
[0012] The present invention relates to, for example, the following <1> ~ <4> .
[0013] <1>
[0014] A slurry comprising carbon black in a liquid medium,
[0015] The average primary particle size of the carbon black is 17 nm or more and 30 nm or less,
[0016] The crystallite size (Lc) of the aforementioned carbon black is above the following,
[0017] In the volume-based particle size distribution of the particle group obtained by combining the secondary particles of carbon black and the tertiary particles formed by aggregation of the secondary particles of the aforementioned carbon black in the aforementioned slurry measured by a laser diffraction / scattering method, D50 (μm) is greater than 0.5 μm and less than 0.9 μm, and the ratio of D50 (μm) to the difference between D10 (μm) and D90 (μm) (D50 / (D90-D10)) is greater than 0.25 and less than 0.5.
[0018] <2>
[0019] The coating liquid for electrode formation is <1> A mixture of the slurry described in, a binder solution containing a binder in a liquid medium, and an active material.
[0020] <3>
[0021] A method for manufacturing an electrode, the electrode comprising a current collector and a mixture layer, the manufacturing method comprising:
[0022] The coating liquid preparation process <1> The slurry described in the above, the binder solution containing the binder in the liquid medium, and the active material are mixed to obtain <2> The electrode forming coating liquid described in;
[0023] A coating step of coating the electrode-forming coating solution on the current collector; and
[0024] The electrode forming step is to remove at least a portion of the liquid medium to form a mixture layer on the current collector, thereby forming an electrode including the current collector and the mixture layer.
[0025] <4>
[0026] A method for manufacturing a battery, comprising: <3> A method for manufacturing an electrode as described in .
[0027] In addition, in this specification, the tilde "-" may be used to indicate a numerical range including the numerical values described before and after it. Specifically, the description of "X to Y" (X, Y are both numerical values) means "X or more and Y or less".
[0028] Effects of the Invention
[0029] According to the present invention, an electrode containing carbon black, having excellent discharge rate characteristics and cycle characteristics of a battery, and having excellent peel strength between a mixture layer and a current collector, and a slurry useful for forming a battery can be provided. In addition, according to the present invention, a method for manufacturing an electrode using the slurry and a method for manufacturing a battery can be provided. DETAILED DESCRIPTION
[0030] Hereinafter, preferred embodiments of the present invention will be described in detail.
[0031] <Slurry>
[0032] The slurry of this embodiment contains carbon black in a liquid medium. In this embodiment, the average primary particle size of the carbon black is 17 nm or more and 30 nm or less, and the crystallite size (Lc) of the carbon black is above In addition, in the volume-based particle size distribution of the slurry of the present embodiment measured by a laser diffraction / scattering method, D50 (μm) is 0.5 μm or more and 0.9 μm or less, and the ratio of D50 (μm) to the difference between D10 (μm) and D90 (μm) (D50 / (D90-D10)) is 0.25 or more and 0.5 or less.
[0033] The slurry of this embodiment is useful for forming a battery electrode such as a lithium ion secondary battery, and by using an electrode formed using the slurry of this embodiment, a battery having excellent discharge rate characteristics and cycle characteristics can be formed. In addition, an electrode and a battery having excellent peel strength between a mixture layer and a current collector can be provided.
[0034] According to the findings of the inventors of the present application, it is believed that by finely dispersing carbon black having an average primary particle size and a crystallite size within the above-mentioned range in a liquid medium in a manner such that D50 and a ratio (D50 / (D90-D10)) are within the above-mentioned range, the carbon black in the slurry becomes in an effective dispersed state for electrode formation, thereby realizing a battery with excellent discharge rate characteristics.
[0035] In more detail, it is believed that the structure of carbon black affects the conductivity during electrode formation, and if the structure develops, a conductive path in the electrode can be effectively formed. On the other hand, the structure of carbon black with a small primary particle size develops in a complexly complexed shape, so the slurry has high viscosity, and uniform dispersion in a liquid medium tends to become difficult. The slurry of the present embodiment can microdisperse carbon black in a liquid medium in a dispersed state that is effective for forming an electrode while maintaining a structure that can form an effective conductive path in the electrode. Therefore, it is believed that according to the slurry of the present embodiment, a battery with excellent discharge rate characteristics can be achieved.
[0036] <Carbon Black>
[0037] In the present embodiment, the carbon black may be acetylene black, furnace black, channel black, or the like, and acetylene black is preferred from the viewpoint of excellent purity and easy acquisition of excellent battery characteristics.
[0038] The average primary particle size of carbon black is 17 nm or more, and may be 18 nm or more, or 19 nm or more. It is believed that by making the average primary particle size of carbon black larger, the interaction between the liquid medium and the conductive material, and the interaction between the conductive materials become smaller, so that it is easy to mix evenly with the active material, and it is easy to form a strong conductive path, so that it is easy to obtain excellent battery characteristics.
[0039] In addition, the average primary particle size of carbon black is 30 nm or less, and may be 29 nm or less, 27 nm or less, 25 nm or less, 23 nm or less, or 21 nm or less. It is believed that by making the average primary particle size of carbon black small, the number of electrical contacts with active materials and conductive materials increases, the conductivity becomes good, and excellent battery characteristics are easily obtained.
[0040] That is, the average primary particle size of carbon black can be, for example, 17 to 30 nm, 17 to 29 nm, 17 to 27 nm, 17 to 25 nm, 17 to 23 nm, 17 to 21 nm, 18 to 30 nm, 18 to 29 nm, 18 to 27 nm, 18 to 25 nm, 18 to 23 nm, 18 to 21 nm, 19 to 30 nm, 19 to 29 nm, 19 to 27 nm, 19 to 25 nm, 19 to 23 nm or 19 to 21 nm.
[0041] The average primary particle size of carbon black refers to the average value of the equivalent circle diameter measured based on the image when observing carbon black using a transmission electron microscope (TEM). Specifically, using a transmission electron microscope JEM-2000FX (manufactured by JEOL Ltd.), 10 images of carbon black are taken at a magnification of 100,000 times. For the obtained images, the equivalent circle diameters of 200 randomly selected primary particles of carbon black are measured by image analysis, and the equivalent circle diameters are obtained by taking the arithmetic average.
[0042] The crystallite size (Lc) of carbon black is The above can also be It is considered that by increasing the crystallite size (Lc) of carbon black, π electrons can easily move in the crystal layer, and a conductive path for transporting electrons from the current collector to the active material can be easily formed, thereby making it easier to obtain excellent battery characteristics.
[0043] In addition, the crystallite size (Lc) of carbon black is The following can also be the following, the following, the following, Below or It is considered that by reducing the crystallite size (Lc) of carbon black, the primary particles of carbon black are more likely to have rounded shapes, so that the interaction between particles is reduced, and it is easier to mix evenly with the active material, and it is easier to form a conductive path, so that excellent battery characteristics are easily obtained.
[0044] That is, the crystallite size (Lc) of carbon black may be, for example,
[0045] or
[0046] The crystallite size (Lc) of carbon black is measured in accordance with JIS R 7651. The crystallite size (Lc) of carbon black refers to the crystallite size in the c-axis direction of the carbon black crystal layer.
[0047] The BET specific surface area of carbon black can be, for example, 100 m 2 / g or more, 120m 2 / g or more, 140m 2 / g or above or 160m 2 When the BET specific surface area of carbon black is large, the number of electrical contacts with the active material and the conductive material increases, the conductivity becomes good, and there is a tendency that more excellent battery characteristics are easily obtained.
[0048] The BET specific surface area of carbon black can be, for example, 500 m 2 / g or less, and 450m 2 / g or less, 400m 2 / g or less, 350m 2 / g or below 300m 2 When the BET specific surface area of carbon black is small, the interaction between the liquid medium and the conductive material, and the interaction between the conductive materials become small, so that it is easy to mix evenly with the active material, and it is easy to form a strong conductive path, so that there is a tendency to easily obtain more excellent battery characteristics.
[0049] That is, the BET specific surface area of carbon black may be, for example, 100 to 500 m 2 / g, 100~450m 2 / g, 100~400m 2 / g, 100~350m 2 / g, 100~300m 2 / g, 120~500m 2 / g, 120~450m 2 / g, 120~400m 2 / g, 120~350m 2 / g, 120~300m 2 / g, 140~500m 2 / g, 140~450m 2 / g, 140~400m 2 / g, 140~350m 2 / g, 140~300m 2 / g, 160~500m 2 / g, 160~450m 2 / g, 160~400m 2 / g, 160~350m 2 / g or 160~300m 2 / g.
[0050] The BET specific surface area of carbon black can be measured by a static capacitance method using nitrogen as an adsorbent in accordance with JIS Z8830.
[0051] When the peak area of the peak with mass number m / z57 detected by thermal desorption spectroscopy of carbon black is set as S1, and the peak area of the peak with mass number m / z128 is set as S2, the ratio of peak area S2 to peak area S1 (S2 / S1) is preferably 0.2 to 1.9. The ratio (S2 / S1) represents the proportion of organic components adsorbed on the surface of carbon black. By making the ratio (S2 / S1) less than 1.9, the organic components adsorbed on the surface of carbon black are sufficiently reduced, and the reduction in conductivity caused by the capture of π electrons by the organic components is significantly suppressed. In addition, by making the ratio (S2 / S1) more than 0.2, the organic components adsorbed on the surface of carbon black act as dispersants, and the dispersibility in the liquid medium is improved, so the slurry viscosity is further reduced. The peak area S1 of the peak with mass number m / z57 and the peak area S2 of the peak with mass number m / z128 can be measured by released gas mass spectrometry (EGA-MS). For example, carbon black is placed in a gas chromatograph-mass spectrometer with a thermal decomposition device, maintained at 50°C for 5 minutes in an atmospheric pressure He gas flow, and then heated to 800°C at a rate of 80°C / min. Mass spectrometry analysis is performed on the components released by the temperature increase, thereby enabling the peak area S1 of the peak with a mass number of m / z 57 and the peak area S2 of the peak with a mass number of m / z 128 to be measured.
[0052] From the viewpoint of better discharge rate characteristics, the ratio (S2 / S1) may be 1.5 or less, 1.0 or less, 0.8 or less, 0.6 or less, 0.5 or less, 0.4 or less, or 0.3 or less. Alternatively, the ratio (S2 / S1) may be 0.25 or more, or 0.3 or more.
[0053] That is, the ratio (S2 / S1) may be, for example, 0.2 to 1.9, 0.2 to 1.5, 0.2 to 1.0, 0.2 to 0.8, 0.2 to 0.6, 0.2 to 0.5, 0.2 to 0.4, 0.2 to 0.3, 0.25 to 1.9, 0.25 to 1.5, 0.25 to 1.0, 0.25 to 0.8, 0.25 to 0.6, 0.25 to 0.5, 0.25 to 0.4, 0.25 to 0.3, 0.3 to 1.9, 0.3 to 1.5, 0.3 to 1.0, 0.3 to 0.8, 0.3 to 0.6, 0.3 to 0.5 or 0.3 to 0.4.
[0054] From the viewpoint of excellent conductivity, the volume resistivity of carbon black may be 0.30 Ω·cm or less or 0.25 Ω·cm or less. The volume resistivity of carbon black is measured, for example, in a state of compression under a load of 7.5 MPa.
[0055] The ash content and water content of carbon black are not particularly limited. The ash content of carbon black may be, for example, 0.04% by mass or less, and the water content of carbon black may be, for example, 0.10% by mass or less.
[0056] The method for producing carbon black is not particularly limited. Carbon black can be produced, for example, by a production method including the following steps: a synthesis step of treating a raw material gas containing hydrocarbons in a cylindrical decomposition furnace to obtain carbon black; and a high purification step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet.
[0057] In the synthesis process, the raw material gas is processed by a cylindrical decomposition furnace. The cylindrical decomposition furnace may include, for example, a thermal decomposition section for performing a thermal decomposition reaction of hydrocarbons, and a maturation section for modifying the thermal decomposition reaction product. The cylindrical decomposition furnace may also include a supply port for supplying the raw material gas to the thermal decomposition section, and a recovery port for recovering the carbon black generated by the maturation section.
[0058] The raw material gas supplied to the thermal decomposition section is preferably retained at a temperature of 1900°C or higher for 30 to 150 seconds. By setting the retention time of the raw material gas to be 30 seconds or more, the formation of carbon aerosol caused by the completion of the thermal decomposition reaction and the development of the chain structure can be more reliably implemented. In addition, by setting the retention time of the raw material gas to be 150 seconds or less, the flocculation of the carbon aerosol is suppressed, so that it is easier to remove magnetic foreign matter in the high-purification process, and it is easy to obtain high-purity carbon black.
[0059] In the aging section, it is preferred that the pyrolysis reaction product supplied from the pyrolysis section be retained at a temperature of 1700°C or higher for 20 to 90 seconds. By making the retention time of the pyrolysis reaction product 20 seconds or more, it is easy to obtain higher quality carbon black by promoting the modification and aggregation of the carbon aerosol. In addition, by making the retention time of the pyrolysis reaction product 90 seconds or less, the flocculation of the carbon aerosol is suppressed, so that it is easier to remove magnetic foreign matter in the high purification process, and it is easy to obtain high-purity carbon black.
[0060] The residence time in the thermal decomposition section and the aging section can be appropriately adjusted by adjusting the gas linear velocity of the circulating gas. The residence time in the aging section is preferably shorter than the residence time in the thermal decomposition section. That is, the gas linear velocity in the aging section is preferably faster than the gas linear velocity in the thermal decomposition section.
[0061] In the present embodiment, the raw gas preferably contains acetylene as a carbon source. The content of the carbon source (e.g., acetylene) in the raw gas is, for example, 10% by volume or more, preferably 20% by volume or more, more preferably 30% by volume or more, or 100% by volume. It should be noted that the content of each component in the raw gas represents a volume ratio based on the volume at 100° C. and 1 atmosphere.
[0062] The raw gas may also contain other hydrocarbons other than the carbon source (e.g., acetylene). As other hydrocarbons, for example, methane, ethane, propane, ethylene, propylene, butadiene, benzene, toluene, xylene, gasoline, kerosene, light oil, heavy oil, etc. can be cited. By adding these other hydrocarbons, the reaction temperature can be changed, and the specific surface area of carbon black can be increased or decreased. Other hydrocarbons are preferably selected from the group consisting of aromatic hydrocarbons such as benzene and toluene and unsaturated hydrocarbons such as ethylene and propylene.
[0063] When the raw material gas contains acetylene and other hydrocarbons, the content of other hydrocarbons is, for example, 0.1 to 99 parts by volume, preferably 0.2 to 50 parts by volume, and more preferably 0.3 to 30 parts by volume per 100 parts by volume of acetylene.
[0064] That is, the content of other hydrocarbons relative to 100 parts by volume of acetylene may be, for example, 0.1 to 99 parts by volume, 0.1 to 50 parts by volume, 0.1 to 30 parts by volume, 0.2 to 99 parts by volume, 0.2 to 50 parts by volume, 0.2 to 30 parts by volume, 0.3 to 99 parts by volume, 0.3 to 50 parts by volume, or 0.3 to 30 parts by volume.
[0065] The raw material gas may also contain water vapor gas, oxygen, hydrogen gas, carbon dioxide gas, etc. As these gases, it is preferred to use high-purity gases of 99.9% by volume or more. By using such high-purity gases, it is easy to produce carbon black with less magnetic foreign matter, stable BET specific surface area and oil absorption.
[0066] The content of water vapor gas can be, for example, 0 to 80 parts by volume, preferably 0.1 to 70 parts by volume, more preferably 1 to 60 parts by volume, and further preferably 3 to 55 parts by volume, relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas. If the content of water vapor gas is within the above range, the BET specific surface area of carbon black tends to become larger.
[0067] That is, the content of water vapor gas relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw gas may be, for example, 0 to 80 parts by volume, 0 to 70 parts by volume, 0 to 60 parts by volume, 0 to 55 parts by volume, 0.1 to 80 parts by volume, 0.1 to 70 parts by volume, 0.1 to 60 parts by volume, 0.1 to 55 parts by volume, 1 to 80 parts by volume, 1 to 70 parts by volume, 1 to 60 parts by volume, 1 to 55 parts by volume, 3 to 80 parts by volume, 3 to 70 parts by volume, 3 to 60 parts by volume, or 3 to 55 parts by volume.
[0068] In the synthesis step, oxygen is preferably supplied to the thermal decomposition section together with the raw material gas, and more preferably supplied to the thermal decomposition section by injecting oxygen from around a supply port for supplying the raw material gas to the thermal decomposition section.
[0069] The cylindrical decomposition furnace preferably has an oxygen injection port near the raw gas supply port, and more preferably has a plurality of injection ports arranged at equal intervals to surround the supply port. The number of injection ports is preferably 3 or more, and more preferably 3 to 8.
[0070] In addition, the cylindrical decomposition furnace may also be provided with a nozzle of a multi-layer tube structure (e.g., a double-layer tube structure, a triple-layer tube structure, etc.) having a supply port for the raw gas and a nozzle for injecting oxygen from the periphery thereof. In the case of a double-layer tube structure, for example, the raw gas may be injected from the gap portion on the inner tube side, and the oxygen may be injected from the gap portion on the outer tube side. In the case of a triple-layer tube structure formed of an inner tube, a middle tube, and an outer tube, for example, oxygen may be injected from the gap portion formed by the outer wall of the middle tube and the inner wall of the outer tube, and the raw gas may be injected from the remaining gap portion.
[0071] The injection amount of oxygen is not particularly limited without considering the yield of carbon black. Even if more oxygen is injected than the required limit, carbon black can be produced. Relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw gas, the injection amount of oxygen can be, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, or 0 to 200 parts by volume, preferably 0.1 to 190 parts by volume, more preferably 0.5 to 180 parts by volume, and further preferably 1 to 160 parts by volume. If the injection amount of oxygen increases, the BET specific surface area of carbon black and the above-mentioned ratio (S2 / S1) tend to become larger, and if the injection amount of oxygen decreases, the average primary particle size of carbon black tends to become larger.
[0072] That is, the injection amount of oxygen gas relative to 100 parts by volume of the carbon source (e.g., acetylene) in the raw material gas may be, for example, 0 to 300 parts by volume, 0 to 250 parts by volume, 0 to 220 parts by volume, 0 to 200 parts by volume, 0 to 190 parts by volume, 0 to 180 parts by volume, 0 to 160 parts by volume, 0.1 to 300 parts by volume, 0.1 to 250 parts by volume, 0.1 to 220 parts by volume, 0.1 to 200 parts by volume, 0.1 ... .1-180 parts by volume, 0.1-160 parts by volume, 0.5-300 parts by volume, 0.5-250 parts by volume, 0.5-220 parts by volume, 0.5-200 parts by volume, 0.5-190 parts by volume, 0.5-180 parts by volume, 0.5-160 parts by volume, 1-300 parts by volume, 1-250 parts by volume, 1-220 parts by volume, 1-200 parts by volume, 1-190 parts by volume, 1-180 parts by volume or 1-160 parts by volume.
[0073] In the synthesis process, for example, by adjusting the addition rate of hydrocarbons other than acetylene, the amount of oxygen injected, etc., the average primary particle size, BET specific surface area, and crystallite size (Lc) of the obtained carbon black can be adjusted.
[0074] The high-purification step is a step of removing magnetic foreign matter from the carbon black obtained in the synthesis step using a magnet. The high-purification step may be a step of, for example, contacting the carbon black obtained in the synthesis step with a magnet, or placing it near a magnet (for example, passing it near a magnet) to remove magnetic foreign matter from the carbon black.
[0075] The maximum surface flux density of the magnet is not particularly limited, and may be, for example, 700 mT or more, preferably 1000 mT or more, and more preferably 1200 mT or more. As a result, fine magnetic foreign matter attached to carbon black is more strongly adsorbed, so it is easy to obtain carbon black with a lower nickel content. The upper limit of the maximum surface flux density of the magnet is not particularly limited, and may be, for example, 1400 mT or less.
[0076] That is, the maximum surface magnetic flux density of the magnet may be, for example, 700 to 1400 mT, 1000 to 1400 mT, or 1200 to 1400 mT.
[0077] In the high purification step, the magnetic foreign matter may be removed from the carbon black in such a manner that the nickel content is 50 ppb or less (preferably 40 ppb or less, more preferably 30 ppb or less, and further preferably 20 ppb or less). The lower limit of the nickel content is not particularly limited, and the nickel content in the carbon black may be, for example, 1 ppb or more, and from the viewpoint of cost and productivity, may be 10 ppb or more, or 15 ppb or more.
[0078] That is, the nickel content in carbon black may be, for example, 1 to 50 ppb, 1 to 40 ppb, 1 to 30 ppb, 1 to 20 ppb, 10 to 50 ppb, 10 to 40 ppb, 10 to 30 ppb, 10 to 20 ppb, 15 to 50 ppb, 15 to 40 ppb, 15 to 30 ppb or 15 to 20 ppb.
[0079] <Liquid medium>
[0080] The liquid medium is not particularly limited as long as it is a dispersion medium that can finely disperse carbon black. Examples of the liquid medium include water, N-methyl-2-pyrrolidone, cyclohexane, methyl ethyl ketone, methyl isobutyl ketone, etc. Among them, N-methyl-2-pyrrolidone is preferred from the viewpoint of easy dispersibility of carbon black. It should be noted that in this specification, N-methyl-2-pyrrolidone is sometimes referred to as "NMP".
[0081] The content of carbon black in the slurry of the present embodiment can be, for example, 1% by mass or more, 3% by mass or more, 5% by mass or more, or 10% by mass or more. If the content of carbon black is high, it is easy to prepare a coating liquid for electrode formation with a high solid content concentration. In addition, the content of carbon black in the slurry of the present embodiment is based on the total amount of the slurry, for example, 30% by mass or less, 25% by mass or less, 20% by mass or less, or 15% by mass or less. If the content of carbon black is small, it is easy to obtain a coating liquid for electrode formation with low viscosity, and when applying the coating liquid for electrode formation, it is easy to obtain a uniform electrode.
[0082] That is, the content of carbon black in the slurry of the present embodiment can be, for example, 1-30 mass%, 1-25 mass%, 1-20 mass%, 1-15 mass%, 3-30 mass%, 3-25 mass%, 3-20 mass%, 3-15 mass%, 5-30 mass%, 5-25 mass%, 5-20 mass%, 5-15 mass%, 10-30 mass%, 10-25 mass%, 10-20 mass% or 10-15 mass%.
[0083] <Dispersant>
[0084] The slurry of the present embodiment may further contain a dispersant. The dispersant may be any component as long as it has a function of assisting the fine dispersion of carbon black in a liquid medium.
[0085] Examples of the dispersant include polymer dispersants and low molecular weight dispersants. From the viewpoint of long-term dispersion stability of carbon black, polymer dispersants are preferred.
[0086] The dispersant may be, for example, a dispersant selected from the group consisting of polyvinyl alcohol, polyvinyl pyrrolidone, polyvinyl butyral, carboxymethyl cellulose and salts thereof, polyvinyl acetal, polyvinyl acetate, polyvinyl amine, and polyvinyl formal.
[0087] Relative to 100 parts by mass of carbon black, the content of the dispersant in the slurry of the present embodiment may be, for example, 1 part by mass or more, or 3 parts by mass or more, 7 parts by mass or more, or 11 parts by mass or more. If the content of the dispersant is high, the conductive material is easily micro-dispersed more evenly, thereby having a tendency to easily obtain more excellent battery characteristics. In addition, relative to 100 parts by mass of carbon black, the content of the dispersant in the slurry of the present embodiment may be, for example, 50 parts by mass or less, or 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less. If the content of the dispersant is low, the insulating component in the electrode-forming coating solution is reduced, and the resistance of the electrode is reduced, thereby having a tendency to easily obtain more excellent battery characteristics.
[0088] That is, relative to 100 parts by mass of carbon black, the content of the dispersant in the slurry of the present embodiment can be, for example, 1 to 50 parts by mass, 1 to 30 parts by mass, 1 to 20 parts by mass, 1 to 15 parts by mass, 3 to 50 parts by mass, 3 to 30 parts by mass, 3 to 20 parts by mass, 3 to 15 parts by mass, 7 to 50 parts by mass, 7 to 30 parts by mass, 7 to 20 parts by mass, 7 to 15 parts by mass, 11 to 50 parts by mass, 11 to 30 parts by mass, 11 to 20 parts by mass, 11 to 15 parts by mass.
[0089] <Particle Size Distribution of Carbon Black Particles in Slurry>
[0090] The volume-based particle size distribution of a particle group obtained by combining secondary particles of carbon black and tertiary particles formed by aggregation of the secondary particles of carbon black in the slurry of the present embodiment is measured by a laser diffraction / scattering method. Specifically, the measurement is performed under the following conditions.
[0091] ·Measurement equipment: Laser diffraction and scattering type particle size distribution measuring device (manufactured by Microtrac Bell, model Microtrac MT3300EXII)
[0092] ·Measurement conditions: Measurement range / 0.02-2000μm, Particle transmittance / Absorption, Particle shape / Non-spherical, Solvent / NMP, Circulation output / 5
[0093] Sample input amount: The slurry was added and adjusted so that the transmittance (TR) displayed when the sample was input was 0.85 to 0.9.
[0094] It should be noted that the secondary particles of the aforementioned carbon black refer to particles formed by chemical bonding of primary particles of carbon black, which are generally called aggregates in the classification based on the structure of carbon black. In addition, the tertiary particles of the aforementioned carbon black refer to particles generally called agglomerates.
[0095] In this specification, D10 refers to the particle size (10% diameter) (μm) when the cumulative value in the above particle size distribution is 10%, D50 refers to the particle size (50% diameter) (μm) when the cumulative value in the above particle size distribution is 50%, and D90 refers to the particle size (90% diameter) (μm) when the cumulative value in the above particle size distribution is 90%.
[0096] The D50 in the particle size distribution is 0.5 μm or more, and may be 0.6 μm or more, or 0.7 μm or more. In addition, the D50 in the particle size distribution is 0.9 μm or less.
[0097] That is, D50 in the above-mentioned particle size distribution may be, for example, 0.5 to 0.9 μm, 0.6 to 0.9 μm, or 0.7 to 0.9 μm.
[0098] The ratio of the difference between D50 and D10 and D90 in the particle size distribution (D50 / (D90-D10)) is 0.25 or more, and may be 0.26 or more, or 0.27 or more. In addition, the ratio of the difference between D50 and D10 and D90 in the particle size distribution (D50 / (D90-D10)) is 0.5 or less, and may be 0.48 or less, or 0.46 or less.
[0099] That is, the ratio of D50 to the difference between D10 and D90 in the above-mentioned particle size distribution (D50 / (D90-D10)) may be, for example, 0.25-0.5, 0.25-0.48, 0.25-0.46, 0.26-0.5, 0.26-0.48, 0.26-0.46, 0.27-0.5, 0.27-0.48 or 0.27-0.46.
[0100] When D50 and the ratio (D50 / (D90-D10)) in the slurry of the present embodiment are within the above ranges, carbon black can efficiently form a conductive path in the electrode, and carbon black can be finely dispersed in an appropriate dispersed state in the electrode-forming coating liquid described later.
[0101] In the present embodiment, D50 and the ratio (D50 / (D90-D10)) can be adjusted by appropriately selecting a mixing method (for example, a stirring method, a stirring time, etc.) when forming the slurry.
[0102] <Other ingredients>
[0103] The slurry of the present embodiment may further contain other components besides carbon black, a dispersant, and a liquid medium. Examples of other components include carbon nanotubes, graphite, graphene, a binder, a dispersion stabilizer, and a defoaming agent.
[0104] The content of other components in the slurry of the present embodiment may be, for example, 10% by mass or less, 5% by mass or less, 3% by mass or less, 1% by mass or less, 0.5% by mass or less, 0.1% by mass or less, or 0% by mass.
[0105] <Viscosity of slurry>
[0106] From the viewpoint of increasing the solid content concentration of the electrode-forming coating liquid and easily obtaining a uniform positive electrode, the viscosity of the slurry of the present embodiment at 25° C. and a shear rate of 10 (1 / sec) is preferably 100 to 1300 mPa·sec, for example.
[0107] <Method for producing slurry>
[0108] The slurry of the present embodiment can be produced by mixing carbon black, a liquid medium, and a dispersant as needed, and mixing and finely dispersing the carbon black secondary particles and tertiary particles in the liquid medium so as to exhibit the predetermined particle size distribution of the present invention.
[0109] The mixing / microdispersion method is not particularly limited and can be implemented by known methods (e.g., mixing and stirring using a bead mill, a ball mill, a sand mill, a twin-screw mixer, a self-rotating and revolving mixer, a planetary mixer, a dispersing mixer, etc.). These methods and devices can also be used in combination as appropriate.
[0110] The various conditions in the mixing / microdispersion method can be appropriately adjusted so that D50 and the ratio (D50 / (D90-D10)) are within the above range. For example, by extending the stirring time, D50 tends to decrease, and the ratio (D50 / (D90-D10)) tends to increase. In addition, by shortening the stirring time, D50 tends to increase, and the ratio (D50 / (D90-D10)) tends to decrease.
[0111] <Method for producing electrode>
[0112] The manufacturing method of the electrode of the present embodiment comprises: a coating liquid preparation step, in which a slurry, a binder solution containing a binder in a liquid medium, and an active material are mixed to obtain a coating liquid for electrode formation; a coating step, in which the coating liquid for electrode formation is coated on a current collector; and an electrode forming step, in which at least a portion of the liquid medium is removed to form a mixture layer on the current collector, thereby forming an electrode including the current collector and the mixture layer.
[0113] <Binder Solution>
[0114] The aforementioned binder solution is a solution containing a binder in a liquid medium.
[0115] Examples of the liquid medium in the binder solution include the same medium as the liquid medium in the slurry. The liquid medium in the binder solution may be the same as or different from the liquid medium in the slurry, but is preferably the same.
[0116] Examples of the binder include polyvinylidene fluoride, polytetrafluoroethylene, styrene butadiene copolymer, and (meth)acrylate copolymer. The structure of the polymer of the binder may be, for example, a random copolymer, an alternating copolymer, a graft copolymer, a block copolymer, etc. From the viewpoint of excellent voltage resistance, polyvinylidene fluoride is preferred as the binder.
[0117] The binder solution may further contain other components in addition to the binder and the liquid medium. Examples of other components in the binder solution include a conductive material, a thickener, and a surfactant.
[0118] The solid content concentration in the binder solution is not particularly limited, and may be, for example, 1% by mass or more, 2% by mass or more, or 3% by mass or more. In addition, the solid content concentration in the binder solution may be, for example, 15% by mass or less, 13% by mass or less, or 10% by mass or less.
[0119] That is, the solid content concentration in the binder solution may be, for example, 1-15 mass %, 1-13 mass %, 1-10 mass %, 2-15 mass %, 2-13 mass %, 2-10 mass %, 3-15 mass %, 3-13 mass % or 3-10 mass %.
[0120] <Active substances>
[0121] The active material is not particularly limited, and for example, either a positive electrode active material or a negative electrode active material can be selected and used.
[0122] The type of positive electrode active material is not particularly limited, as long as it is a material that can reversibly absorb and release cations. For example, the positive electrode active material may include a material having a volume resistivity of 1×10 4 Ω·cm or more manganese-containing lithium composite oxide or lithium-containing polyanion compound. Examples of the lithium-containing composite oxide containing manganese include LiMnO2, LiMnO3, LiMn2O3, Li 1+x Mn 2-x O4 (where x = 0 to 0.33) and other lithium manganese oxides; LiMn x Ni y Co z O2 (where x+y+z=1, 0≤y<1, 0≤z<1, 0≤x<1), Li 1+x Mn 2-x-y M y O4 (where x = 0 to 0.33, y = 0 to 1.0, 2-xy>0), LiMn 2-x M x O2 (where x = 0.01 to 0.1), Li2Mn3MO8 and other composite oxides containing one or more transition metal elements. As lithium-containing polyanion compounds, polyanion compounds such as LiFePO4, LiMnPO4, Li2MPO4F (where M is at least one metal selected from Co, Ni, Fe, Cr, and Zn) can be cited. M in each composition formula is at least one selected from the group consisting of Fe, Co, Ni, Al, Cu, Mg, Cr, Zn, and Ta.
[0123] The active material may be a negative electrode active material. Examples of the negative electrode active material include carbonaceous materials such as natural graphite, artificial graphite, graphite, activated carbon, coke, needle coke, fluidized coke, mesophase microbeads, carbon fibers, and pyrolytic carbon.
[0124] <Coating liquid preparation process>
[0125] The method for mixing the various components in the coating liquid preparation step is not particularly limited, and the mixture can be mixed by a known method (for example, stirring and mixing using a ball mill, sand mill, twin-screw kneader, orbiting mixer, planetary mixer, disperser, etc.).
[0126] The electrode-forming coating liquid contains: carbon black contained in the slurry, a binder contained in the binder solution, an active material, and a liquid medium independently contained in the slurry and the binder solution. In addition to the liquid medium independently contained in the slurry and the binder solution, the electrode-forming coating liquid may also contain a liquid medium (additional liquid medium) used in the coating liquid preparation process. The electrode-forming coating liquid may also contain a dispersant.
[0127] The content of carbon black in the electrode-forming coating liquid may be, for example, 0.01% by mass or more, 0.04% by mass or more, 0.07% by mass or more, or 0.1% by mass or more, based on the total amount of solid components. In addition, the content of carbon black in the electrode-forming coating liquid may be, for example, 8% by mass or less, 7% by mass or less, 6% by mass or less, or 5% by mass or less, based on the total amount of solid components.
[0128] That is, based on the total amount of solid components, the content of carbon black in the electrode forming coating liquid can be, for example, 0.01 to 8 mass%, 0.01 to 7 mass%, 0.01 to 6 mass%, 0.01 to 5 mass%, 0.04 to 8 mass%, 0.04 to 7 mass%, 0.04 to 6 mass%, 0.04 to 5 mass%, 0.07 to 8 mass%, 0.07 to 7 mass%, 0.07 to 6 mass%, 0.07 to 5 mass%, 0.1 to 8 mass%, 0.1 to 7 mass%, 0.1 to 6 mass% or 0.1 to 5 mass%.
[0129] Based on the total amount of solid components, the content of the binder in the electrode-forming coating liquid can be, for example, 0.01% by mass or more, 0.02% by mass or more, 0.03% by mass or more, 0.04% by mass or more, or 0.05% by mass or more. In addition, based on the total amount of solid components, the content of the binder in the electrode-forming coating liquid can be, for example, 10% by mass or less, 8% by mass or less, 6% by mass or less, or 4% by mass or less.
[0130] That is, based on the total amount of solid components, the content of the binder in the electrode forming coating liquid can be, for example, 0.01 to 10 mass%, 0.01 to 8 mass%, 0.01 to 6 mass%, 0.01 to 4 mass%, 0.02 to 10 mass%, 0.02 to 8 mass%, 0.02 to 6 mass%, 0.02 to 4 mass%, 0.03 to 10 mass%, 0.03 to 8 mass%, 0.03 to 6 mass%, 0.03 to 4 mass%, 0.04 to 10 mass%, 0.04 to 8 mass%, 0.04 to 6 mass%, 0.04 to 4 mass%, 0.05 to 10 mass%, 0.05 to 8 mass%, 0.05 to 6 mass% or 0.05 to 4 mass%.
[0131] The content of the active material in the electrode-forming coating liquid may be, for example, 70% by mass or more, 75% by mass or more, or 80% by mass or more, based on the total amount of the solid component. In addition, the content of the active material in the electrode-forming coating liquid may be, for example, 99% by mass or less, 98.9% by mass or less, or 98.8% by mass or less, based on the total amount of the solid component.
[0132] That is, based on the total amount of solid components, the content of active material in the electrode forming coating liquid can be, for example, 70 to 99 mass%, 70 to 98.9 mass%, 70 to 98.8 mass%, 75 to 99 mass%, 75 to 98.9 mass%, 75 to 98.8 mass%, 80 to 99 mass%, 80 to 98.9 mass% or 80 to 98.8 mass%.
[0133] Based on the total amount of solid components, the content of the dispersant in the electrode-forming coating liquid can be, for example, 0.001% by mass or more, 0.004% by mass or more, 0.007% by mass or more, or 0.01% by mass or more. In addition, based on the total amount of solid components, the content of the dispersant in the electrode-forming coating liquid can be, for example, 0.8% by mass or less, 0.7% by mass or less, 0.6% by mass or less, or 0.5% by mass or less.
[0134] That is, based on the total amount of solid components, the content of the dispersant in the electrode forming coating liquid can be, for example, 0.001 to 0.8 mass%, 0.001 to 0.7 mass%, 0.001 to 0.6 mass%, 0.001 to 0.5 mass%, 0.004 to 0.8 mass%, 0.004 to 0.7 mass%, 0.004 to 0.6 mass%, 0.004 to 0.5 mass%, 0.007 to 0.8 mass%, 0.007 to 0.7 mass%, 0.007 to 0.6 mass%, 0.007 to 0.5 mass%, 0.01 to 0.8 mass%, 0.01 to 0.7 mass%, 0.01 to 0.6 mass% or 0.01 to 0.5 mass%.
[0135] The content of the dispersant in the electrode-forming coating liquid may be, for example, 1 part by mass or more, 3 parts by mass or more, 7 parts by mass or more, or 11 parts by mass or more relative to 100 parts by mass of carbon black. In addition, the content of the dispersant in the electrode-forming coating liquid may be, for example, 50 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less relative to 100 parts by mass of carbon black.
[0136] That is, relative to 100 parts by mass of carbon black, the content of the dispersant in the electrode forming coating liquid can be, for example, 1 to 50 parts by mass, 1 to 30 parts by mass, 1 to 20 parts by mass, 1 to 15 parts by mass, 3 to 50 parts by mass, 3 to 30 parts by mass, 3 to 20 parts by mass, 3 to 15 parts by mass, 7 to 50 parts by mass, 7 to 30 parts by mass, 7 to 20 parts by mass, 7 to 15 parts by mass, 11 to 50 parts by mass, 11 to 30 parts by mass, 11 to 20 parts by mass or 11 to 15 parts by mass.
[0137] The solid content concentration of the electrode-forming coating liquid, i.e., the carbon black and dispersant introduced from the aforementioned slurry in the electrode-forming coating liquid, and the concentration of the ratio of the substantial binder and active material, can be, for example, 50% by mass or more, or 55% by mass or more, 60% by mass or more, or 65% by mass or more. In addition, the solid content concentration of the electrode-forming coating liquid can be, for example, 90% by mass or less, or 85% by mass or less, 82% by mass or less, 77% by mass or less, 75% by mass or less, 73% by mass or less, or 70% by mass or less.
[0138] That is, the solid content concentration of the electrode forming coating liquid can be, for example, 50-90 mass%, 50-85 mass%, 50-82 mass%, 50-77 mass%, 50-75 mass%, 50-73 mass%, 50-70 mass%, 55-90 mass%, 55-85 mass%, 55-82 mass%, 55-77 mass%, 55-75 mass%, 55-73 mass%, 55-70 mass%, 60-90 mass%, 60-85 mass%, 60-82 mass%, 60-77 mass%, 60-75 mass%, 60-73 mass%, 60-70 mass%, 65-90 mass%, 65-85 mass%, 65-82 mass%, 65-77 mass%, 65-75 mass%, 65-73 mass% or 65-70 mass%.
[0139] <Electrode Formation Process>
[0140] In the electrode forming step, the electrode forming coating liquid is applied to the current collector to form a composite layer on the current collector. Thus, an electrode including the current collector and the composite layer can be obtained. The composite layer is a layer containing the solid components (carbon black, binder and active material (and further dispersant as required)) in the electrode forming coating liquid, and can be a layer formed by removing at least a portion of the liquid medium from the electrode forming coating liquid.
[0141] The current collector is not particularly limited, and known current collectors can be used without particular limitation. As the current collector, for example, metal foil (metals such as gold, silver, copper, platinum, aluminum, iron, nickel, chromium, manganese, lead, tungsten, and titanium, and alloys with any of them as the main component) is used. Among them, aluminum is preferably used for the positive electrode, and copper is preferably used for the negative electrode. The current collector is generally provided in the form of foil, but is not limited thereto, and a perforated foil-shaped and mesh-shaped current collector can also be used.
[0142] The method for coating the electrode-forming coating liquid on the collector is not particularly limited, and examples thereof include die coating, dip coating, roll coating, blade coating, spray coating, gravure coating, screen printing, and electrostatic coating.
[0143] The amount of the electrode-forming coating liquid applied is not particularly limited, and can be appropriately adjusted so that the thickness of the mixture layer falls within a desired range.
[0144] The mixture layer can be formed by removing at least a portion of the liquid medium from the coating film of the electrode forming coating liquid formed on the collector. The method for removing the liquid medium is not particularly limited, and for example, as a method for removing by vaporizing at least a portion of the liquid medium by heating and / or reducing pressure, there can be cited drying, air supply drying machine, warm air drying machine, infrared heating machine, far infrared heating machine, etc.
[0145] The method for manufacturing an electrode of the present embodiment may further include a pressurizing step of pressurizing the mixture layer and the current collector formed in the electrode forming step in a stacking direction. The pressurizing step can bring the mixture layer and the current collector into close contact with each other.
[0146] The pressing method in the pressing step is not particularly limited, and for example, it may be a method such as roll pressing, die pressing, or calendar pressing.
[0147] The thickness of the mixture layer in the electrode is not particularly limited, and can be, for example, 50 μm or more. From the perspective of high capacity of the battery, it is preferably 55 μm or more, more preferably 60 μm or more, and can also be 65 μm or more or 70 μm or more. In addition, the thickness of the mixture layer in the electrode can be, for example, 150 μm or less, and from the perspective of further improving the discharge rate characteristics, it is preferably 140 μm or less, more preferably 130 μm or less, and can also be 120 μm or less or 110 μm or less.
[0148] That is, the thickness of the mixture layer in the electrode can be, for example, 50 to 150 μm, 50 to 140 μm, 50 to 130 μm, 50 to 120 μm, 50 to 110 μm, 55 to 150 μm, 55 to 140 μm, 55 to 130 μm, 55 to 120 μm, 55 to 110 μm, 60 to 150 μm, 60 to 140 μm, 60 to 130 μm, 60 to 120 μm, 60 to 110 μm, 65 to 150 μm, 65 to 140 μm, 65 to 130 μm, 65 to 120 μm, 65 to 110 μm, 70 to 150 μm, 70 to 140 μm, 70 to 130 μm, 70 to 120 μm or 70 to 110 μm.
[0149] The electrode produced by the production method of this embodiment can be suitably used as an electrode of a battery, particularly a secondary battery (lithium ion secondary battery).
[0150] The electrode of the present embodiment is an electrode including a mixture layer containing carbon black, an active material, and a binder, and the mixture layer may further contain a dispersant. The electrode of the present embodiment may be, for example, a positive electrode manufactured by the above-mentioned manufacturing method.
[0151] The battery in this embodiment (preferably a secondary battery, more preferably a lithium ion secondary battery) includes a positive electrode manufactured by the above-mentioned manufacturing method. In the battery in this embodiment, the structure other than the positive electrode may be the same as that of a known battery.
[0152] The use of the battery in this embodiment is not particularly limited, and it can be used in a wide range of fields, for example, in digital cameras, camcorders, portable audio players, portable LCD TVs and other portable AV devices, notebook personal computers, smart phones, mobile PCs and other portable information terminals, as well as portable game devices, power tools, electric bicycles, hybrid vehicles, electric vehicles, power storage systems, etc.
[0153] As mentioned above, although the preferred embodiment of the present invention was described, the present invention is not limited to the above-mentioned embodiment.
[0154] Example
[0155] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0156] <Example 1>
[0157] (Manufacture of Carbon Black A)
[0158] Acetylene (12 Nm) as a raw material was supplied from a nozzle installed in the upstream part of the carbon black reaction furnace (furnace length 6 m, furnace diameter 0.65 m). 3 / h, toluene 32kg / h, oxygen 20Nm3 / h to produce carbon black, which is captured by a bag filter installed in the downstream part of the reactor. Then, it is passed through a dry cyclone device and an iron removal magnet and recovered in a tank. It should be noted that acetylene, toluene and oxygen are supplied to the reactor after being heated to 115°C to obtain carbon black A. The obtained carbon black A has an average primary particle size of 20nm and a crystallite size (Lc) of BET specific surface area is 240m 2 / g.
[0159] In addition, carbon black A was placed in a released gas mass spectrometer (GC / MS: manufactured by Shimadzu Corporation, QP-2010, pyrolyzer: manufactured by Frontier Lab, Py-2020iD), and after being kept at 50°C for 5 minutes in an atmospheric pressure He gas flow, the temperature was raised to 800°C at 80°C / min, and mass spectrometry analysis of the components released by the temperature increase was performed under the following conditions, and the peak area S1 of the peak with a mass number of m / z 57 and the peak area S2 of the peak with a mass number of m / z 128 of the obtained carbon black A were measured. The ratio (S2 / S1) was calculated from the peak area S1 of the peak with a mass number of m / z 57 and the peak area S2 of the peak with a mass number of m / z 128 of the measured carbon black A, and the result was 0.40.
[0160] Chromatographic column: Ultra ALLOY-DTM manufactured by Frontier Lab (length 2.5m, 0.15mm I.D, 0.47mm O.D)
[0161] Sample introduction temperature: 300℃
[0162] Column temperature: 300°C, maintain for 80 minutes
[0163] Split ratio: 30:1
[0164] Column flow rate: 1.0mL / min
[0165] Ionization method: EI
[0166] Determination of mass number range: m / z = 10 ~ 200
[0167] (Manufacturing of slurry)
[0168] 1.4 mass % of polyvinyl alcohol (Poval B05 manufactured by Denka, saponification degree: 87%) and 12.0 mass % of carbon black A as a dispersant were added to 86.6 mass % of NMP as a liquid medium, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 54 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to obtain the slurry of Example 1.
[0169] The frequency distribution and cumulative distribution of the volume-based particle size of the carbon black in the obtained slurry were measured using a laser diffraction / scattering particle size distribution measuring apparatus (manufactured by Microtrac Bell, model Microtrac MT3300EXII) according to the following method to determine D10, D50 and D90.
[0170] Measurement conditions: Measurement range / 0.02-2000μm, Particle transmittance / Absorption, Particle shape / Non-spherical, Solvent / NMP, Circulation output / 5
[0171] Sample input amount: Add and adjust the slurry so that it falls within the optimal concentration range displayed when the sample is input.
[0172] (Manufacturing of coating solution for electrode formation)
[0173] The slurry obtained above, NMP solution of polyvinylidene fluoride (binder), lithium nickel cobalt manganese composite oxide LiNi 0.6 Mn 0.2 Co 0.2 O2 (positive electrode active material, manufactured by Beijing Dangsheng Company, "ME6E"), and NMP are adjusted in such a way that the concentration of the solid component, i.e., carbon black and dispersant (1.0 mass parts) brought in from the aforementioned slurry, which in turn becomes a substantial binder (2.0 mass parts), and the positive electrode active material (97 mass parts) (a total of 100 mass parts) becomes 69 mass % of the total electrode forming coating liquid to obtain the electrode forming coating liquid of Example 1.
[0174] (Manufacturing of positive electrode)
[0175] The obtained electrode-forming coating liquid was applied to an aluminum foil (manufactured by UACJ Co., Ltd.) having a thickness of 15 μm using a Baker-type coater, and dried at 105° C. for 1 hour to completely remove NMP. Thereafter, the foil was pressed and cut to produce a positive electrode.
[0176] (Manufacturing of negative electrode)
[0177] Pure water (manufactured by Kanto Chemical Co., Ltd.) as a solvent, artificial graphite (manufactured by Hitachi Chemical Co., Ltd., "MAG-D") as a negative electrode active material, styrene butadiene rubber (manufactured by Zeon Co., Ltd., "BM-400B", hereinafter referred to as SBR) as a binder, carboxymethyl cellulose (manufactured by Daicel Co., Ltd., "D2200", hereinafter referred to as CMC) as a dispersant, and carbon black (manufactured by Denka Co., Ltd., "Li-400") as a conductive material were prepared. Next, CMC was weighed and mixed so that the solid content was 1% by mass, carbon black was 1% by mass, and artificial graphite was weighed and mixed so that the solid content was 96% by mass, and pure water was added to the mixture, and the mixture was mixed until uniform using a rotation-revolution mixer (manufactured by Thinky Co., Ltd., Awatori Rentaro ARV-310) to obtain a mixture. Next, SBR is weighed in a manner that the solid content is 2% by mass, added to the resulting mixture, and mixed evenly using a rotation-revolution mixer (manufactured by Thinky, Awatori Rentaro ARV-310) to obtain a negative electrode coating liquid. Next, the negative electrode coating liquid is formed into a film on a copper foil (manufactured by UACJ) having a thickness of 10 μm using an applicator to make a laminate, which is left to stand in a dryer and pre-dried at 60 ° C for 1 hour. Next, a roller press is used to press at a linear pressure of 50 kg / cm, and the laminate is prepared in a manner that the thickness of the entire laminate becomes 60 μm. Next, vacuum drying is performed at 120 ° C for 3 hours to completely remove residual moisture to obtain a negative electrode having a collector and a mixture layer.
[0178] (Battery manufacturing)
[0179] After the positive electrode, separator, and negative electrode are overlapped and stacked, they are packaged and pre-sealed with an aluminum laminate film, and then an electrolyte is injected, and the battery is molded and vacuum-sealed to produce a laminated secondary battery.
[0180] (Battery Evaluation)
[0181] Evaluations of the batteries in the examples and comparative examples showing the effects of the present invention were all measured by the methods described in the description of Example 1. It should be noted that, except for Table 4, it is appropriate to compare these results in the same table using the same type of carbon black.
[0182] [Discharge rate characteristics (rate capacity maintenance ratio)]
[0183] After the manufactured battery was charged at 4.3V and 0.2C controlled constant current and constant voltage at 25°C, it was discharged to 3.0V at a constant current of 0.2C. Next, after recovery charging was performed again at 4.3V and 0.2C controlled constant current and constant voltage, it was discharged to 3.0V at a constant current of 0.2C, and the discharge capacity at this time was measured. Next, the recovery charging conditions were set to 4.3V and 0.2C controlled constant current and constant voltage, and charging was performed. On the other hand, the discharge current was changed step by step to 0.5C, 1C, 2C, and 3C, and the recovery charging and discharging were repeated to measure the discharge capacity relative to each discharge current. As an indicator of the discharge rate characteristics of the battery, the capacity retention rate during 3C discharge relative to 0.2C discharge was calculated as the rate capacity retention rate.
[0184] [Cycle characteristics (cycle capacity maintenance rate)]
[0185] The prepared battery was charged at 4.3V and 1C controlled constant current and constant voltage at 25°C, and then discharged to 3.0V at a constant current of 1C. The above charge and discharge were repeated for 500 cycles, and the discharge capacity in each cycle was measured. As an indicator of the cycle characteristics of the battery, the capacity retention rate after 500 cycles was calculated relative to the capacity retention rate after 1 cycle as the cycle capacity retention rate.
[0186] [Peel strength]
[0187] The electrode-forming coating liquid was applied onto an aluminum foil (produced by UACJ Co., Ltd.) having a thickness of 15 μm using a Baker-type coater, and dried at 105° C. for 1 hour to completely remove NMP.
[0188] Then, the positive electrode was pressed and cut, and a 180°C peel test was performed on the positive electrode using a peel strength tester (AGS-X manufactured by Shimadzu Corporation). In the peel test, the positive electrode was subjected to a 180°C peel test at a unit area weight of 19.5 to 20 mg / cm 2 、Density 3.4mg / cm 3 The peel strength between the aluminum foil and the electrode mixture was measured under the conditions of 2 cm test piece width and 50 mm / min tensile speed. The average test force N in the range of 30 to 70 mm stroke width of the electrode plate after peeling was calculated as the peel strength.
[0189] <Example 2>
[0190] (Manufacturing of slurry)
[0191] 1.4% by mass of polyvinyl alcohol (Poval B05 manufactured by Denka, saponification degree: 87%) and 12.0% by mass of carbon black A as a dispersant were added to 86.6% by mass of NMP, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 60 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to obtain the slurry of Example 2.
[0192] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0193] <Example 3>
[0194] (Manufacturing of slurry)
[0195] 1.4% by mass of polyvinyl alcohol (Poval B05 manufactured by Denka, degree of saponification: 87%) and 12.0% by mass of carbon black A as a dispersant were added to 86.6% by mass of NMP, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 45 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare the slurry of Example 3.
[0196] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0197] <Comparative Example 1>
[0198] (Manufacturing of slurry)
[0199] 1.4% by mass of polyvinyl alcohol (Poval B05 manufactured by Denka, degree of saponification: 87%) and 12.0% by mass of carbon black A as a dispersant were added to 86.6% by mass of NMP, and stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 18 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 1.
[0200] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0201] <Comparative Example 2>
[0202] (Manufacturing of slurry)
[0203] 1.4% by mass of polyvinyl alcohol (Poval B05 manufactured by Denka, degree of saponification: 87%) and 12.0% by mass of carbon black A as a dispersant were added to 86.6% by mass of NMP, and stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 198 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 2.
[0204] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0205] The evaluation results of Examples 1 to 3 and Comparative Examples 1 and 2 are shown in Table 1. In addition, in the table, CB represents carbon black, and CBA represents carbon black A. The same applies to the following tables.
[0206] [Table 1]
[0207]
[0208] <Example 4>
[0209] (Manufacturing of coating solution for electrode formation)
[0210] The slurry of Example 3, NMP solution of polyvinylidene fluoride (binder), lithium nickel cobalt manganese composite oxide LiNi 0.6 Mn 0.2 Co 0.2 O2 (positive electrode active material, manufactured by Beijing Dangsheng Co., Ltd., "ME6E"), and NMP are mixed in such a manner that carbon black becomes 1.0 mass parts, binder becomes 1.3 mass parts, positive electrode active material becomes 97.7 mass parts, and solid content concentration becomes 69.5 mass% to obtain a coating liquid for electrode formation.
[0211] Using the obtained electrode-forming coating solution, a positive electrode, a negative electrode, and a battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0212] <Example 5>
[0213] (Manufacturing of coating solution for electrode formation)
[0214] The slurry of Example 3, NMP solution of polyvinylidene fluoride (binder), lithium nickel cobalt manganese composite oxide LiNi 0.6 Mn 0.2 Co 0.2 O2 (positive electrode active material, manufactured by Beijing Dangsheng Co., Ltd., "ME6E"), and NMP are mixed in such a manner that carbon black becomes 1.0 mass part, binder becomes 2.5 mass parts, positive electrode active material becomes 96.5 mass parts, and solid content concentration becomes 64.5 mass% to obtain a coating liquid for electrode formation.
[0215] Using the obtained electrode-forming coating solution, a positive electrode, a negative electrode, and a battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0216] <Comparative Example 3>
[0217] (Manufacturing of coating solution for electrode formation)
[0218] The slurry of Comparative Example 1, NMP solution of polyvinylidene fluoride (binder), lithium nickel cobalt manganese composite oxide LiNi 0.6 Mn 0.2 Co 0.2 O2 (positive electrode active material, manufactured by Beijing Dangsheng Co., Ltd., "ME6E"), and NMP are mixed in such a manner that carbon black becomes 1.0 mass parts, binder becomes 1.3 mass parts, positive electrode active material becomes 97.7 mass parts, and solid content concentration becomes 69.5 mass% to obtain a coating liquid for electrode formation.
[0219] Using the obtained electrode-forming coating solution, a positive electrode, a negative electrode, and a battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0220] <Comparative Example 4>
[0221] (Manufacturing of coating solution for electrode formation)
[0222] The slurry of Comparative Example 1, NMP solution of polyvinylidene fluoride (binder), lithium nickel cobalt manganese composite oxide LiNi 0.6 Mn 0.2 Co 0.2 O2 (positive electrode active material, manufactured by Beijing Dangsheng Co., Ltd., "ME6E"), and NMP are mixed in such a manner that carbon black becomes 1.0 mass part, binder becomes 2.5 mass parts, positive electrode active material becomes 96.5 mass parts, and solid content concentration becomes 64.5 mass% to obtain a coating liquid for electrode formation.
[0223] Using the obtained electrode-forming coating solution, a positive electrode, a negative electrode, and a battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0224] Table 2 shows the evaluation results of Examples 4 and 5 and Comparative Examples 3 and 4.
[0225] [Table 2]
[0226]
[0227] <Example 6>
[0228] (Manufacturing of slurry)
[0229] To 85.6% by mass of NMP, 0.9% by mass of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, saponification degree: 87%) and carbon black (Li-435 manufactured by Denka, average primary particle size: 26 nm, crystallite size (Lc): 0.9% by mass) as a dispersant were added. BET specific surface area: 133m 2 / g, ratio (S2 / S1): 0.23) 13.5% by mass, using a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.), stirring at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 45 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare the slurry of Example 6.
[0230] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0231] <Example 7>
[0232] (Manufacturing of slurry)
[0233] 0.9 mass % of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, saponification degree: 87%) and 13.5 mass % of carbon black (Li-435 manufactured by Denka) as a dispersant were added to 85.6 mass % of NMP, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 50 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare the slurry of Example 7.
[0234] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0235] <Example 8>
[0236] (Manufacturing of slurry)
[0237] 0.9 mass % of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, saponification degree: 87%) and 13.5 mass % of carbon black (Li-435 manufactured by Denka) as a dispersant were added to 85.6 mass % of NMP, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 36 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare the slurry of Example 8.
[0238] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0239] <Comparative Example 5>
[0240] (Manufacturing of slurry)
[0241] 0.9 mass % of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, saponification degree: 87%) and 13.5 mass % of carbon black (Li-435 manufactured by Denka) as a dispersant were added to 85.6 mass % of NMP, and the mixture was stirred at 70 rpm for 3 hours using a planetary mixer (Hivismix 3D-5 manufactured by Primix Co., Ltd.) to prepare a slurry containing carbon black. The obtained slurry was dispersed for 8 minutes using a bead mill (Mugen Flow MGF2-ZA manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 5.
[0242] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0243] <Comparative Example 6>
[0244] (Manufacturing of slurry)
[0245] To 85.6% by mass of NMP, 0.9% by mass of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, degree of saponification: 87%) and 13.5% by mass of carbon black (Li-435, manufactured by Denka) as a dispersant were added, and a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.) was used to stir at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 154 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 6.
[0246] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0247] Table 3 shows the evaluation results of Examples 6 to 8 and Comparative Examples 5 to 6.
[0248] [Table 3]
[0249]
[0250] <Comparative Example 7>
[0251] (Manufacturing of slurry)
[0252] To 89.7% by mass of NMP were added 1.3% by mass of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, degree of saponification: 87%) as a dispersant and carbon black (BLACK PEARLS 1000 manufactured by Cabot Corporation, average primary particle size: 16 nm, crystallite size (Lc): BET specific surface area: 343m 2 / g, ratio (S2 / S1): 3.42) 9.0 mass %, using a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.), stirring at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 45 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 7.
[0253] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0254] <Comparative Example 8>
[0255] (Manufacturing of slurry)
[0256] To 87.6% by mass of NMP were added 1.7% by mass of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, degree of saponification: 87%) as a dispersant and carbon black (ECP, manufactured by Lion, average primary particle size: 40 nm, crystallite size (Lc): BET specific surface area: 820m 2 / g, ratio (S2 / S1): 2.06) 10.7% by mass, using a planetary mixer (Hivismix3D-5, manufactured by Primix Co., Ltd.), stirring at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 55 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 8.
[0257] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0258] <Comparative Example 9>
[0259] (Manufacturing of slurry)
[0260] To 80.7% by mass of NMP were added 1.3% by mass of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, degree of saponification: 87%) as a dispersant and carbon black (SuperPLi, manufactured by Imerys Graphite & Carbon, average primary particle size: 36 nm, crystallite size (Lc): BET specific surface area: 62m 2 / g, ratio (S2 / S1): 1.12) 18.0 mass %, using a planetary mixer (Hivismix 3D-5, manufactured by Primix Co., Ltd.), stirring at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 20 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 9.
[0261] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0262] <Comparative Example 10>
[0263] (Manufacturing of slurry)
[0264] To 83.5 mass % of NMP, 1.5 mass % of polyvinyl alcohol (Poval DR-1137 manufactured by Denka, saponification degree: 87%) and carbon black (YS manufactured by Orion, average primary particle size: 26 nm, crystallite size (Lc): 2.5% were added as a dispersant. BET specific surface area: 120m 2 / g, ratio (S2 / S1): 0.92) 15.0 mass %, using a planetary mixer (Hivismix3D-5, manufactured by Primix Co., Ltd.), stirring at 70 rpm for 3 hours to prepare a slurry containing carbon black. The obtained slurry was dispersed for 35 minutes using a bead mill (Mugen Flow MGF2-ZA, manufactured by Ashizawa Finetech Co., Ltd.) equipped with zirconia balls (diameter 0.5 mm) at a slurry flow rate of 1 kg / min and a mill peripheral speed of 8 m / s. After the dispersion treatment, the zirconia balls were removed by filtration to prepare a slurry of Comparative Example 10.
[0265] Using this slurry, the electrode-forming coating liquid, the positive electrode, the negative electrode, and the battery were produced in the same manner as in Example 1, and various evaluations were performed.
[0266] Table 4 shows the evaluation results of Comparative Examples 7 to 10.
[0267] [Table 4]
[0268]
Claims
1. A slurry comprising carbon black in a liquid medium, The average primary particle size of the carbon black is 17 nm or more and 30 nm or less. The crystallite size (Lc) of the carbon black is above the following, In the volume-based particle size distribution of the particle group obtained by combining the secondary particles of carbon black and the tertiary particles formed by aggregation of the secondary particles of the carbon black in the slurry measured by the laser diffraction and scattering method, D50 (μm) is greater than 0.5 μm and less than 0.9 μm, and the ratio of D50 (μm) to the difference between D10 (μm) and D90 (μm) (D50 / (D90-D10)) is greater than 0.25 and less than 0.
5.
2. A coating liquid for electrode formation, which is a mixture of the slurry according to claim 1, a binder solution containing a binder in a liquid medium, and an active material.
3. A method for manufacturing an electrode, the electrode comprising a current collector and a mixture layer, the method comprising: A coating liquid preparation step of mixing the slurry according to claim 1, a binder solution containing a binder in a liquid medium, and an active material to obtain the electrode forming coating liquid according to claim 2; A coating step of coating the electrode-forming coating solution on a current collector; and The electrode forming step is to remove at least a portion of the liquid medium to form a mixture layer on the current collector, thereby forming an electrode including the current collector and the mixture layer.
4. A method for producing a battery, comprising the method for producing an electrode according to claim 3.
Citation Information
Patent Citations
Conductive slurry, electrode slurry and electrode for electric double-layer capacitor using the slurry
JP2008227481A